The Divine Comedy, Volume 2. - Alighieri, Dante (Galaxy Books., 1961)
An invaluable source of pleasure to those English readers who wish to read this great medieval classic with true understanding, Sinclair's three-volume prose translation of Dante's Divine Comedy provides both the original Italian text and the Sinclair translation, arranged on facing pages, and commentaries, appearing after each canto, which serve as brilliant examples of genuine literary criticism. This volume contains the complete translation of Dante's Purgatorio.